Catalyst prepared from waste polyester fabric and nickel-containing solid waste as well as preparation method and application of catalyst

By using waste polyester spinning and nickel-containing solid waste to prepare MOF catalysts, the problems of high catalyst costs and difficult waste disposal in the prior art are solved, and the low-cost and environmentally friendly carbon dioxide cracking effect is achieved.

CN119463204AActive Publication Date: 2025-02-18ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411511766.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The high price of catalysts used in the prior art leads to an increase in usage costs. At the same time, the treatment and utilization of waste polyester and metallurgical solid waste have problems such as environmental pollution and resource waste.

Method used

The catalyst is prepared by using waste polyester spinning and nickel-containing solid waste. The specific steps include preparing nickel-containing solid waste into nickel ferrite and combining it with the BDC extracted from the waste polyester spinning to form a metal organic frame (MOF) catalyst.

Benefits of technology

The preparation of low-cost catalysts is realized, which can effectively crack carbon dioxide, and reduce environmental pollution and resource waste through comprehensive utilization of waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463204A_ABST
    Figure CN119463204A_ABST
Patent Text Reader

Abstract

According to the catalyst prepared from the waste polyester fabric and the nickel-containing solid waste, the preparation method and the application, the catalyst is prepared by loading BDC and a metallurgical solid waste product nickel ferrite through a water solvent method, the MOF catalyst is large in specific surface area and excellent in catalytic effect, the activity of a loaded compound is high, and the CO2 cracking effect exceeds that of a single catalyst. Compared with the prior art, the method has the advantages that by introducing the catalyst formed by converting the waste polyester fabric and the nickel-containing solid waste, important progress can be made in the aspects of environmental governance and resource utilization, and CO2 can be cracked by using the obtained catalyst while the waste is comprehensively utilized, so that the concentration of CO2 in the atmosphere is reduced; and a new thought and a new direction are provided for promoting sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst preparation, and in particular relates to a catalyst prepared by utilizing waste polyester textiles and nickel-containing solid waste, a preparation method and application thereof. Background Art

[0002] In recent years, excessive emissions of greenhouse gases have affected the global ecological environment, and the concentration of carbon dioxide in the atmosphere has exceeded 400ppm, which will have a negative impact on the climate and environment. In response to this problem, more and more studies have been conducted on reducing carbon dioxide emissions. There are many existing measures to reduce carbon emissions, such as reducing the use of fossil energy, improving energy efficiency, promoting clean production technology, promoting forest regeneration, and developing carbon capture and storage technology (CCS). Carbon capture and storage technology (CCS) is an important way to reduce carbon emissions. It can convert carbon dioxide into carbon-based materials, but it is difficult to industrialize and has poor economic benefits. These shortcomings make low-temperature plasma (LTP) cracking carbon dioxide a more promising solution. Low-temperature plasma (LTP) cracking carbon dioxide can operate at lower temperatures and pressures, can generate valuable CO and CH3OH, and can use solid waste as a catalyst to improve resource utilization efficiency. Therefore, low-temperature plasma (LTP) cracking carbon dioxide is considered to be a better and effective solution.

[0003] On June 6, 2024, Cheng He, Lei Xiaoting, Zhang Wenchao, and Lu Xinpei reviewed the research progress of different types of LTP in the conversion of CO2 in the paper "Research on the Conversion of CO2 by Low-Temperature Plasma and Decomposition Mechanism" [High Voltage Technology]. However, the catalysts used in the existing technology are relatively expensive, resulting in an increase in the cost of use. Therefore, it is particularly necessary to develop a low-cost catalyst.

[0004] The treatment and utilization of waste polyester and metallurgical solid waste is also an issue of widespread concern. As one of the most widely used synthetic fibers in the world, my country's polyester production reached 53.63 million tons in 2021, an increase of 8.94% year-on-year. However, due to its good stability in the environment, polyester is difficult to degrade in nature. Traditional methods of treating waste polyester, such as incineration and landfill, can solve the problem in the short term, but they will lead to waste of resources and pollution, and seriously endanger the environment and human health. Metallurgical nickel-containing solid waste contains a large amount of harmful substances. Nickel and other metal elements are difficult to decompose in nature, and long-term accumulation may lead to soil deterioration. Therefore, improper treatment of metallurgical nickel-containing solid waste will cause serious damage to the surrounding ecological environment.

[0005] Therefore, providing a technology that can simultaneously crack carbon dioxide and utilize waste materials has broad application prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a catalyst prepared by using waste polyester textiles and nickel-containing solid waste and a preparation method. The present invention provides a method for preparing a catalyst by using waste polyester textiles and nickel-containing solid waste, prepares nickel ferrite by using nickel-containing solid waste, prepares BDC (phthalate) by using waste polyester textiles, and prepares MOF catalyst by using BDC and nickel ferrite, which can comprehensively utilize waste and reduce environmental pollution.

[0007] Another object of the present invention is to provide an application of a catalyst prepared by using waste polyester textiles and nickel-containing solid waste for cracking carbon dioxide.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a catalyst using waste polyester textiles and nickel-containing solid waste comprises the following steps:

[0010] 1) drying, grinding and roasting the nickel-containing solid waste to obtain nickel ferrite;

[0011] 2) After the waste polyester fabric is washed, dried, mixed with alkali in water, heated for reaction, centrifuged, the pH of the supernatant is adjusted to acidic, pH 0.5-1.5, and centrifuged again to obtain BDC;

[0012] 3) The nickel ferrite prepared in step 1) and the BDC prepared in step 2) are mixed in an organic solvent, and heated to react to obtain a catalyst.

[0013] In step 1), the nickel-containing solid waste has a nickel content of greater than 15% by mass and is derived from NiSO4, and an iron content of greater than 20% by mass.

[0014] In step 1), the drying refers to drying at 90°C overnight for 10-12 hours;

[0015] In step 1), the nickel-containing solid waste is dried, cooled, ground, sieved through 200 mesh, and the resulting powder is collected.

[0016] In step 1), the calcination refers to heating at 5°C / min to 1000°C and keeping at 1000°C for 4 hours;

[0017] In step 1), after calcination, the product is ground in a mortar and sieved through 200 meshes, and the sieved product is the obtained nickel ferrite.

[0018] Preferably, step 1) is: spreading the ground and sieved nickel-containing solid waste in a crucible, and gently compacting it with a wooden stick to ensure that the powder is not higher than the crucible; placing the crucible in a muffle furnace and roasting it under the conditions of 5°C / min heating to 1000°C, and keeping it at 1000°C for 4 hours; after cooling to room temperature, taking out the crucible, putting the solid waste roasting product into a mortar and grinding it, sieving it through 200 mesh, and the sieved product is the obtained nickel ferrite.

[0019] In step 1), carbonaceous matter in the solid waste is burned to generate carbonaceous gas, and iron oxide and nickel oxide react to generate nickel ferrite.

[0020] In step 2), the drying is carried out in an oven at 80° C. for 2 hours;

[0021] Preferably, in step 2), the polyester textile is discarded, and the polyester clothing is cut into pieces with a size of 1.2 cm×1.5 cm using scissors, and then the pieces are cleaned with clean water and alcohol and then dried.

[0022] In step 2), the waste polyester textile is polyester or waste polyester textile with a polyester purity greater than 90%.

[0023] In step 2), the mass ratio of the waste polyester textile to the alkali is 1:0.3-0.6;

[0024] The base is selected from sodium hydroxide NaOH;

[0025] In step 2), the mass ratio of the waste polyester textile to water is 1:10;

[0026] In step 2), the heating reaction is carried out at 160-220° C. for 6 hours;

[0027] In step 2), after heating reaction, alkali solution is added to the reactant to adjust the pH to 12-13, and then centrifuged; the centrifugal speed is 2500-8000r / min, centrifuged for 6 minutes, and the supernatant is collected. The alkali solution used is 2mol / L NaOH solution.

[0028] In step 2), the pH of the supernatant is adjusted to acid washing, which means that the pH value of the system is adjusted to 0.5-1.5 with HCl solution; the HCl solution with a mass concentration of 36%-38% is used.

[0029] In step 2), the centrifugation is repeated under the centrifugation conditions of 5 minutes at 2500-8000 r / min. After the centrifugation is completed, the supernatant is poured out, leaving the product as a white precipitate.

[0030] Furthermore, the white precipitate was mixed with pure water and washed three times, then washed with ethanol twice, and finally the precipitate was placed in a vacuum drying oven at 90°C and dried for 12 hours. The obtained product was BDC. In this step, the hydrolysis process of polyester under alkaline conditions includes disordered breakage of molecular chains, OH - It reacts with the carbonyl carbon, generates an intermediate (phthalate) and is converted into disodium terephthalate (BDC) and ethylene glycol.

[0031] In step 3), the mass ratio of the nickel ferrite prepared in step 1) to the BDC prepared in step 2) is 0.19-0.21:1;

[0032] In step 3), the nickel ferrite prepared in step 1) and the organic solvent are used in a ratio of 0.70-0.75 mg / mL;

[0033] In step 3), the organic solvent is selected from N,N-dimethylformamide and anhydrous ethanol; the volume ratio of N,N-dimethylformamide to anhydrous ethanol is 16:1;

[0034] In step 3), the heating reaction refers to: heating the reaction at 180° C. for 48 hours.

[0035] In step 3), nickel ferrite reacts with BDC to generate Ni-MOF, and BDC provides phthalate to coordinate with nickel ferrite to form a new metal organic framework. The carboxyl group of BDC can coordinate with nickel ions, thereby stabilizing the structure and promoting its polymerization.

[0036] In step 3), after heating for reaction, cooling, washing with water and ethanol by centrifugation, placing in an oven at 90° C. and drying for 3 hours, the catalyst is obtained.

[0037] The present invention provides a catalyst prepared by using waste polyester textiles and nickel-containing solid waste, which is prepared by the above method.

[0038] An application of a catalyst prepared by using waste polyester textiles and nickel-containing solid waste for cracking carbon dioxide.

[0039] The specific method is: mix the catalyst and filler evenly for ionization and cracking of CO2, the ionization voltage is 1kv, and the current needs to be controlled at 1A.

[0040] The mass ratio of the catalyst to the filler is 1:80-110;

[0041] The filler is 0.3-0.8 mm SiO2 glass beads; the filler includes but is not limited to SiO2 glass microbeads, and Al2O3, ZrO2 and BaTiO3 microbeads can also be used as filling materials. These filling materials can generate a large electron energy density and electric field strength during the discharge process; at the same time, they have a large specific surface area, and after being added, they can provide more surfaces for CO2 molecules to adsorb, thereby increasing the contact opportunities between reactants and catalysts or active sites and improving the reaction rate. Furthermore, and more importantly, the above-mentioned filling materials can be used as carriers to improve the dispersion of catalysts and prevent catalyst particles from agglomerating, which is conducive to increasing the number of effective active sites and further improving cracking efficiency.

[0042] The inventors found that the application of solid waste alone to prepare catalysts mainly uses metal elements and compounds in solid waste as active components, but the active components are limited and it is difficult to improve the performance of the catalyst. The present invention uses a water solvent method to load BDC and nickel ferrite, a metallurgical solid waste product, to prepare a catalyst. The MOF catalyst has a large specific surface area, excellent catalytic effect, high activity of the loaded compound, and a CO2 cracking effect that exceeds that of a single catalyst. The catalytic effect of the catalyst prepared by exploring different mass ratios of BDC and nickel ferrite was found to be the best by comparison.

[0043] Compared with the prior art, the present invention can make important progress in environmental governance and resource utilization by introducing catalysts transformed from waste polyester textiles and nickel-containing solid waste. While comprehensively utilizing the waste, the obtained catalyst can also be used to crack CO2 to reduce the CO2 concentration in the atmosphere, providing new ideas and directions for promoting sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention;

[0045] Figure 2 Characterization diagram of BDC, nickel ferrite and MOF catalysts;

[0046] Figure 3 This is the XRD pattern of BDC. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0049] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0050] Example 1

[0051] A method for preparing a catalyst using waste polyester textiles and nickel-containing solid waste comprises the following steps:

[0052] 1) The metallurgical electroplating waste liquid filter material generated when a steel plant cleans the electroplating process is used as nickel-containing solid waste, wherein the nickel element mass percentage content is 18% and exists in the form of NiSO4, the iron element mass percentage content is 33% and the source is leached in steel production, and dried overnight at 90°C for 10 hours. After drying, it is cooled, ground, and sieved through 200 meshes to collect the resulting powder; the sieved nickel-containing solid waste is spread flat in a crucible and gently compacted with a wooden stick to ensure that the powder is not higher than the crucible. The crucible is placed in a muffle furnace for roasting. The roasting conditions are 5°C / min heating, heating to 1000°C, and keeping warm at 1000°C for 4 hours. After cooling to room temperature, take out the crucible, grind the solid waste roasting product into a mortar, sieve through 200 meshes, and the sieved product is the obtained nickel ferrite, and its component detection is shown in Table 1.

[0053] Table 1 Main compound composition and element composition of nickel ferrite (mass percentage)

[0054] Compound Mass percentage element Mass percentage <![CDATA[NiFe2O4]]> 71.52 Fe 33.56 <![CDATA[SiO2]]> 15.04 Ni 18.5 <![CDATA[Al2O3]]> 3.74 Si 7.03 CaO 2.9 Al 1.98

[0055] The remaining impurities are not shown in Table 1.

[0056] It can be seen from Table 1 that after calcination, the main component of the material is NiFe2O4, and the main elements are Fe and Ni. Among them, SiO2 behaves mildly in the catalytic effect and has no effect on the catalytic process.

[0057] 2) Select discarded polyester clothing (discarded polyester textiles with a polyester purity greater than 90%), cut the polyester clothing into pieces of about 1.2 cm × 1.5 cm with scissors, then clean the pieces with water and alcohol, and then dry them in an oven at 80°C for 2 hours; add 3.0 g of dried discarded polyester pieces, 1.25 g of NaOH solid and 30 ml of water into a 100 ml tetrafluoroethylene autoclave, cover the autoclave tightly and put it into an oven, heat it to 200°C for 70 minutes, and keep it at 200°C for 6 hours. After cooling to room temperature, take out the autoclave solution and pour it into a beaker.

[0058] Then take 2 mol / l NaOH solution to adjust the pH of the solution in the beaker to 12.5. Use a pipette to fill this solution with pH = 12.5 into a 15 ml centrifuge tube. Place the centrifuge tube in a centrifuge and centrifuge at a speed of 3000r / min for 6 minutes. After the centrifugation is completed, take the supernatant into a beaker. Use a 36% mass concentration HCl solution to adjust the pH value of the system to 1.2, and the resulting solution is a milky white solution. Pour this solution into a centrifuge tube and separate the white precipitate BDC by centrifugation at a centrifugation condition of 5 minutes at 3000r / min. After the centrifugation is completed, pour out the supernatant and leave the product as a white precipitate. Take 5 ml of pure water and pour it into a test tube, mix the white precipitate and pure water and wash them. Then wash them twice with 5 ml of ethanol respectively. The final precipitate is the product, and the product is placed in a vacuum drying oven and dried at 90°C for 12 hours. The product is BDC, and its XRD characterization is as follows Figure 3 As shown, the main component is BDC (C8H6O4).

[0059] 3) Add 64.0 mL DMF and 4.0 mL C2H5OH to the beaker and stir evenly; then, add 249 mg BDC and 50 mg nickel ferrite and stir well to dissolve and disperse. Finally, put it into a high-pressure reactor and heat it at 180°C for 48 hours. After cooling, wash it with water and ethanol by centrifugation for 5 times, put it into an oven at 90°C and dry it for 3 hours. The obtained product is the obtained catalyst.

[0060] An application of a catalyst prepared by using waste polyester textiles and nickel-containing solid waste for cracking carbon dioxide, specifically:

[0061] The catalyst prepared in Example 1 using waste polyester textiles and nickel-containing solid waste was used to crack carbon dioxide. The specific method was to mix the catalyst prepared in Example 1 (60 mg) with filler (0.5 mm SiO2 glass beads, 5 g) and evenly use them for the ionization cracking of CO2. The ionization voltage was 1 kv, the current needed to be controlled at about 1 A, the reactor needed to be cooled by water to prevent the temperature from being too high, and the carbon dioxide flow rate was 24-30 ml / min.

[0062] Figure 2 Characterization diagrams of BDC, nickel ferrite and MOF catalysts. BDC: presents a distinct stripe structure with a regular crystal structure, and each stripe structure has a certain amount of stacking, showing good crystallinity, which helps to improve the catalytic performance. Nickel ferrite: The surface is rough and the morphology is complex, which is conducive to the coupling of other substances to improve the surface activity of the catalyst. Catalyst: The catalyst exhibits a flower-like flake structure with obvious flake characteristics and good porosity, so it has a large specific surface area, which is conducive to the adsorption of gases and is an excellent catalytic material.

[0063] Example 2 (for comparison)

[0064] The difference between this embodiment and embodiment 1 is that no catalyst is added during filling, and only 5 g of glass beads are added.

[0065] Example 3 (for comparison)

[0066] The catalytic process of this embodiment is different from that of embodiment 1 in that the catalyst preparation method is different, that is, the mass ratio of BDC to nickel ferrite is different. 500 mg of nickel ferrite and 249 mg of BDC are put into a tetrafluoroethylene reactor and heated in a water bath. The obtained catalyst is the catalyst in embodiment 3.

[0067] Example 4 (for comparison)

[0068] The catalytic process of this embodiment is different from that of embodiment 1 in that the catalyst preparation method is different, that is, 50 mg of calcium ferrite and 249 mg of BDC are selected for water bath, and the water bath heating conditions remain unchanged. The obtained catalyst is the catalyst of embodiment 4.

[0069] Example 5 (for comparison)

[0070] The catalytic process of this embodiment is different from that of embodiment 1 in that the catalyst preparation method is different, that is, 500 mg of calcium ferrite and 249 mg of BDC are selected for water bath, and the water bath heating conditions remain unchanged. The obtained catalyst is the catalyst of embodiment 5.

[0071] Example 6 (for comparison)

[0072] The catalytic process of this embodiment is different from that of Example 1 in that the catalyst preparation method is different, that is, 20 ml (Ni ion concentration 2000 ppm) of nickel-containing waste liquid and 249 mg BDC are selected for water bath, and the water bath heating conditions remain unchanged. The obtained catalyst is the catalyst of Example 4.

[0073] Example 7

[0074] The catalytic process of the embodiment is different from that of embodiment 1 in that the catalyst preparation method is different, that is, the heating time is different, the heating time is 24 hours, and the obtained catalyst is the catalyst in embodiment 7.

[0075] The amount of catalyst used in the above examples is 60 mg.

[0076] The following are the carbon dioxide cracking results of various embodiments as shown in Table 2-Table 8.

[0077] Table 2 Example 1CO2 cracking effect

[0078] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 4.985357 14.86567 80.14627 10 5.010593 14.91905 80.06754 15 5.032176 14.99888 79.96621

[0079] Table 3 Example 2CO2 cracking effect

[0080]

[0081]

[0082] Table 4 Example 3CO2 cracking effect

[0083] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 3.698518 12.53648 83.76115 10 3.698284 12.59838 83.69972 15 3.686881 12.5647 83.74453

[0084] Table 5 Example 4CO2 cracking effect

[0085] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 4.50 14.34 81.16 10 4.53 14.44 81.02 15 4.56 14.47 80.96

[0086] Table 6 Example 5CO2 cracking effect

[0087] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 3.87 12.06 84.06 10 3.90 12.08 84.02 15 3.93 12.11 83.96

[0088] Table 7 Example 6CO2 cracking effect

[0089] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 4.362667 13.40006 82.23336 10 4.352778 13.44165 82.20153 15 4.324208 13.52273 82.14911

[0090] Table 8 Example 7CO2 cracking effect

[0091] Time / min <![CDATA[O2 / %]]> CO / % <![CDATA[CO2 / %]]> 5 4.20025 14.15843 81.63925 10 4.192221 14.08411 81.72148 15 4.190051 14.13062 81.67711

[0092] According to the above embodiments, it can be obtained that appropriate preparation time can ensure the full reaction and uniform distribution of the catalyst, thereby improving its activity and stability. The different mass ratios of BDC and nickel ferrite can affect the electronic structure, acid-base and surface properties of the catalyst. The optimal catalytic ratio is shown in Example 1 after investigation. Iron-nickel catalytic preparation agents usually have good thermal stability and can maintain activity in high temperature and complex reaction environments. In addition, iron-nickel elements can enhance the electronic conductivity of the catalyst compared to iron-calcium elements, thereby improving the efficiency of the reaction. So overall, embodiment 1 has the best catalytic effect.

[0093] The present invention is a method for preparing a catalyst using discarded clothing polyester and metallurgical solid waste and its application. The catalyst comprehensively utilizes two kinds of waste to achieve comprehensive utilization and resource utilization of waste, while reducing the harm of waste to the environment, it also reduces the dependence of the catalyst on existing valuable materials. The raw materials for preparing the catalyst prepared by the present invention are almost all from waste materials, the process does not produce toxic substances, and the process cost is low. The catalyst prepared by the present invention is a metal organic framework catalyst, which has a larger specific surface area and more active sites, so that CO2 and the catalyst are better in contact, and the catalytic effect of the catalyst is improved. And the catalyst has high thermal stability and chemical stability, and can be reused many times.

[0094] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst using waste polyester textiles and nickel-containing solid waste, characterized in that: The preparation method comprises the following steps: 1) drying, grinding and roasting the nickel-containing solid waste to obtain nickel ferrite; 2) After the waste polyester fabric is washed, dried, mixed with alkali in water, heated for reaction, centrifuged, the pH of the supernatant is adjusted to acidic, pH 0.5-1.5, and centrifuged again to obtain BDC; 3) The nickel ferrite prepared in step 1) and the BDC prepared in step 2) are mixed in an organic solvent, and heated to react to obtain a catalyst.

2. The preparation method according to claim 1, characterized in that: In step 1), the calcination is carried out at 1000° C. for 4 hours.

3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the waste polyester textile to the alkali is 1:0.3-0.6; the alkali is selected from sodium hydroxide.

4. The preparation method according to claim 1 or 3, characterized in that: In step 2), the mass ratio of the waste polyester textile to water is 1:

10.

5. The preparation method according to claim 1 or 3, characterized in that: In step 2), the heating reaction is carried out at 160-220° C. for 6 hours.

6. The preparation method according to claim 1 or 3, characterized in that: In step 2), the pH of the supernatant is adjusted to acidic, and the pH value of the system is adjusted to 0.5-1.5 with HCl solution.

7. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of the nickel ferrite prepared in step 1) to the BDC prepared in step 2) is 0.19-0.21:1; the amount ratio of the nickel ferrite prepared in step 1) to the organic solvent is 0.70-0.75 mg / mL; the organic solvent is selected from N,N-dimethylformamide and anhydrous ethanol; the volume ratio of N,N-dimethylformamide to anhydrous ethanol is 16:

1.

8. The preparation method according to claim 1 or 7, characterized in that: In step 3), the heating reaction refers to: heating the reaction at 180° C. for 48 hours.

9. A catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst according to claim 9, characterized in that: Used to crack carbon dioxide.

Citation Information

Patent Citations

  • Method for preparing unsaturated polyester resin through microwave hydrolysis of waste polyester textile fabrics

    CN110172140A

  • Nickel ferrite metal organic framework derivative nano material and preparation method and application thereof

    CN111584837A

  • Process method for recovering polyester

    CN118684870A

  • Preparation method for and use of covalent organic framework material for co 2 desorption

    WO2024119699A1